The blue green algal bloom in the nearshore waters of Cukai bay facing the South China Sea - Shamsudin, Lokman (Kluwer Academic PublishersDordrecht, Netherlands, 1999)
Since the early 1990's, large areas of mangrove forest along the nearshore waters of Cukai bay had been cleared to give way for the development of aquaculture activities, human settlement and setting up of new small scale fish processing industries. The Cukai bay, facing the South China Sea, has inflows from the Cukai river estuaries and other numerous small river tributaries. The water quality examined (April 1993 to March 1994) in the bay indicated that the ammonium, nitrate and phosphorus contents were high during the pre-wet monsoon (October 1993) with values of 28.2, 30.1 and 29.6 μg L-1, respectively. The source of nutrients in the estuary were from the newly established fish processing cottage industries, nearby fish culture activities, agro-based effluents (mainly fertilisers from surrounding paddy plantations), untreated human (from nearby villages) and animal wastes (from domestic cattle and goat farms) and siltation due to erosion from land development. The main bulk of the microplankton were comprised of diatoms, dinoflagellates, ciliophora and blue green algae. The blue green algae encountered were species of Lyngbya, Oscillatoria, Phormodium and Trichodesmium while those of diatom were species of Asterionella, Chaetoceros, Coscinodiscus, Navicula and Nitzschia. Peak microplankton production in the water column occurred in October 1993, reaching a maximum value of 173 μg CL-1d-1. This comprised primarily of the blue green alga, Trichodesmium thiebautii.; Since the early 1990's, large areas of mangrove forest along the nearshore waters of Cukai bay had been cleared to give way for the development of aquaculture activities, human settlement and setting up of new small scale fish processing industries. The Cukai bay, facing the South China Sea, has inflows from the Cukai river estuaries and other numerous small river tributaries. The water quality examined (April 1993 to March 1994) in the bay indicated that the ammonium, nitrate and phosphorus contents were high during the pre-wet monsoon (October 1993) with values of 28.2, 30.1 and 29.6 μg L-1, respectively. The source of nutrients in the estuary were from the newly established fish processing cottage industries, nearby fish culture activities, agro-based effluents (mainly fertilisers from surrounding paddy plantations), untreated human (from nearby villages) and animal wastes (from domestic cattle and goat farms) and siltation due to erosion from land development. The main bulk of the microplankton were comprised of diatoms, dinoflagellates, ciliophora and blue green algae. The blue green algae encountered were species of Lyngbya, Oscillatoria, Phormodium and Trichodesmium while those of diatom were species of Asterionella, Chaetoceros, Coscinodiscus, Navicula and Nitzschia. Peak microplankton production in the water column occurred in October 1993, reaching a maximum value of 173 μg C L-1 d-1. This comprised primarily of the blue green alga, Trichodesmium thiebautii.